Namibia Human Capital and Knowledge Development for Economic Growth with Equity - Marope, Mmantsetsa Toka (World Bank, Washington, DC, 2021)
The national development framework recognizes knowledge, and its application, as some of the key engines for economic growth and social development. Namibia seeks to transform itself into a knowledge economy. Knowledge economies are built on four pillars: an educated and well-trained population; a dynamic innovation system; an established information and communications infrastructure; and an economic and institutional regime that is conducive to the creation and application of knowledge to promote development. The study adopts a holistic approach to education and training as a system, examining the performance and financing of the system, and the interrelationship of its components; beginning with early childhood education and continuing through higher education. The latter is specifically recognized as a key source of capacity for knowledge creation and application. The study emphasizes the building of a solid foundation for learning through quality basic education as an important starting point towards building a knowledge economy. It also recognizes the need for a balanced sector development, including post-basic education and training. The study lays out a plan for addressing weaknesses of Namibia's education and training system, with priorities identified. This study will prove to be an important part of the road map for Namibia's development and poverty reduction. What should not be lost in the focus on education and training for a knowledge economy is the potential negative impact of HIV/AIDS. Infection rates are among the highest in the world. This scourge alone can sidetrack, and reduce the benefits of initiatives to introduce a knowledge economy.